Supporting care home residents in the last year of life through ‘Needs Rounds’: Development of a pre-implementation programme theory through a rapid collaborative online approach - Macgregor, Aisha; McCormack, Brendan; Spilsbury, Karen; Hockley, Jo; Rutherford, Alasdair; Ogden, Margaret; Soulsby, Irene; McKenzie, Maisie; Hanratty, Barbara; Forbat, Liz (Frontiers in Health Services, 2023)
Background Realist evaluation aims to address the knowledge to practice gap by explaining how an intervention is expected to work, as well as what is likely to impact upon the success of its implementation, by developing programme theories that link contexts, mechanisms and outcomes. Co-production approaches to the development of programme theories offer substantial benefits in addressing power relations, including and valuing different types of knowledge, and promoting buy-in from stakeholders while navigating the complex social systems in which innovations are embedded. This paper describes the co-production of an initial programme theory of how an evidence based intervention developed in Australia - called ‘Palliative Care Needs Rounds’ – might work in England and Scotland to support care home residents approaching their end of life. Methods Using realist evaluation and iPARIHS (integrated Promoting Action on Research Implementation in Health Services) we sought to determine how contexts and mechanisms of change might shape implementation outcomes. Pre-intervention online interviews (n = 28) were conducted (February-April 2021), followed by four co-design online workshops with 43 participants (April-June 2021). The online interviews and workshops included a range of stakeholders, including care home staff, specialist palliative care staff, paramedics, general practitioners, and relatives of people living in care homes. Results This methodology paper reports developments in realist evaluation and co-production methodologies, and how they were used to develop context, mechanisms, outcomes (CMOs) configurations, and chains of inference. The initial (pre-intervention) programme theory is used to illustrate this process. Two developments to iPARIHS are described. First, involving stakeholders in the collaborative co-design workshops created opportunities to commence facilitation. Second, we describe developing iPARIHS’ innovation component, to include novel stakeholder interpretations, perceptions and anticipated use of the intervention as they participated in workshop discussions. Conclusions This rapid and robust co-production methodology draws on interactive collaborative research practices (interviews, workshop discussions of data, illustrative vignettes and visual methods). These innovative and engaging methods can be packaged for online processes to develop, describe and interrogate the CMOs in order to co-produce a programme theory. These approaches also commence facilitation and innovation, and can be adopted in other implementation science and realist studies.